Preparation method of metal oxide coated high-nickel ternary positive electrode material
By covering metal oxides on the surface of high-nickel ternary positive electrode material, the problem of performance attenuation of lithium metal batteries at low temperatures is solved, and the effect of improving lithium ion diffusion coefficient and ion conductivity and improving magnification and cycling performance is achieved.
Patent Information
- Application Number
- CN202411952386.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-14
AI Technical Summary
Lithium metal batteries have rapid performance decays and poor discharge capacity at low temperatures, which limits their application in extremely cold temperatures.
By covering metal oxides on the surface of high-nickel ternary positive electrode material, the positive electrode interface is regulated, the integrity of the surface structure is increased, the interface side reactions are reduced at low temperatures, and a cladding layer is formed to enhance the charge transfer reaction.
It effectively improves the diffusion coefficient and ion conductivity of lithium ions, reduces the diffusion impedance and charge impedance of lithium ions, and improves the rate performance and cycling performance of high-nickel ternary cathode materials at low temperatures.
Smart Images

Figure CN119627086A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium metal battery positive electrode materials, and in particular to a preparation method and application of a metal oxide-coated high-nickel ternary positive electrode material. Background Art
[0002] Lithium metal batteries are the representative of post-lithium-ion batteries, and are expected to significantly increase energy density by utilizing the low operating voltage and high specific capacity (3860mAh / g) of metallic lithium. Lithium metal batteries are currently at a transition point, and the accumulation of basic research knowledge is being transformed into large-scale commercialization. The positive electrode material is the main factor restricting the energy density of lithium metal batteries, and the positive electrode materials currently used on a large scale in the market cannot meet the country's requirements for the energy density of power batteries. Therefore, it is a general trend to use positive electrode materials with higher specific capacity to meet the demand.
[0003] High nickel ternary material LiNi x Mn 1-x-y Co y O2 (NMC) is considered a promising candidate for the next generation of cathode materials due to its high capacity, excellent rate performance and low cost. In practical applications, the temperature in cold regions such as Northeast China is close to -40°C, which requires the battery to work normally in extremely cold weather. However, the rapid performance decay and poor discharge capacity of lithium metal batteries at low temperatures limit their application at extremely cold temperatures. Studies have shown that under extremely cold temperature conditions, due to the increased degree of side reactions caused by the contact between the electrolyte and the cathode interface, the CEI film formed at the cathode interface is too thick and uniform, which hinders the diffusion of lithium ions, resulting in a low depth of discharge, and slow charge transfer at low temperatures, resulting in a decrease in electronic conductivity, a decrease in the diffusion rate of lithium ions, and an increase in the charge transfer impedance at the interface, which seriously affects the practical application of lithium metal batteries at extremely cold temperatures. To address these problems, improving the performance of positive electrode materials at low temperatures can usually be done by doping and coating to improve ion dynamics. Doping with inorganic materials such as Al2O3 and TiO2 will increase interfacial resistance, and the lithium ion diffusion coefficient is low. Using metal oxides to modify the surface of the positive electrode material can effectively increase the diffusion rate at the lithium ion interface, reduce the diffusion impedance at the interface, and improve the performance of lithium-ion batteries at extremely cold temperatures. Summary of the invention
[0004] In view of the problems existing in the above-mentioned high-nickel ternary materials at low temperatures, a method is provided to effectively regulate the cathode interface under low temperature conditions as low as -40°C, increase the integrity of the surface structure, and effectively reduce the interface side reactions at low temperatures. At the same time, the formed coating layer can enhance the charge transfer reaction, has excellent mechanical strength, can stabilize the cathode interface during long-term low-temperature cycles, and greatly improve the stability of low-temperature cycles.
[0005] The present invention is achieved through the following technical solutions: A method for preparing a high-nickel ternary positive electrode material coated with a metal oxide, the steps are as follows: (1) dissolving a solution containing a coated metal in an organic solvent under stirring conditions to obtain a solution containing a metal oxide; (2) adding high nickel ternary material powder to an organic solvent under ultrasonic operation, and ultrasonicating for 10 to 30 minutes to uniformly disperse the high nickel ternary material powder to obtain a solution of high nickel ternary positive electrode material powder; (3) Under ultrasonic operation, the solution containing the metal oxide is dripped into the solution of the high-nickel ternary cathode material powder, so that the solution containing the metal oxide is fully in contact with the high-nickel ternary cathode powder solution. The dispersion and dissolution of the solution containing the metal oxide as a coating and the high-nickel ternary cathode powder will be better, and the two substances will be in better contact during subsequent stirring to obtain a mixed solution; (4) heating the mixed solution under magnetic stirring conditions to evaporate the solvent, collecting the material, and drying it in a vacuum drying oven; (5) The dried material is placed in pure oxygen for calcination to obtain a metal oxide-coated high-nickel ternary positive electrode material.
[0006] The organic solvent in step (1) and step (2) is one of ethanol, hydroxymethane, N-methyl-2-pyrrolidone, N,N-dimethylformamide and isopropanol.
[0007] In the step (1), the solute of the solution containing the coating metal is one of tantalum ethoxide, zirconium ethoxide, niobium ethoxide and tungsten ethoxide.
[0008] The high nickel ternary positive electrode material is LiNi x Co y M 1-x-y O2, wherein M is one of Al, Mn, Mg, Ti, and W, and x≥0.8, 0<y≤1.
[0009] In the step (2), the molar ratio of the metal oxide in the solution containing the coated metal to the high-nickel ternary material powder is 0.5-3:100.
[0010] In the step (2), the molar ratio of the metal oxide in the solution containing the coating metal to the high-nickel ternary material powder is preferably 1-2:100.
[0011] The dropping speed in step (3) is 1.5 to 3.0 mL / min.
[0012] In the step (4), the heating temperature is 50-80° C., the rotation speed is 500-1000 rpm, and the stirring time is 3-8 hours.
[0013] In the step (4), the vacuum drying temperature is 80 to 120° C., and the vacuum drying time is 10 to 18 hours.
[0014] In step 5, the calcination temperature is 600° C. to 800° C., the heating rate is 2° C. to 8° C. / min, and the calcination time is 3 to 8 hours.
[0015] The beneficial effects of the present invention are: The present invention can effectively protect the positive electrode surface at low temperatures, and the coated metal oxide can fill the gaps on the positive electrode surface to reduce the contact area between the electrolyte and the positive electrode; and the metal oxide has good ionic conductivity at the positive electrode interface due to the formed coating layer.
[0016] The high-nickel ternary coating material for lithium batteries prepared by the present invention can effectively increase the diffusion coefficient and ion conductivity of lithium ions at low temperatures, reduce the lithium ion diffusion impedance and charge impedance, and improve the rate performance and cycle performance of the high-nickel ternary positive electrode material at low temperatures.
[0017] The method of the present invention synthesizes a lithium battery ternary positive electrode material coating with high stability. The method is simple and effective, and the surface of the finally obtained material is uniformly coated, which effectively improves the problems existing in the positive electrode at low temperatures. In addition, the requirements for the equipment and process conditions are relatively low, the coating layer particles are fine, the specific surface area is large, the coating effect is better, and it is easier to form a uniform and dense coating on the surface of the ternary material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 SEM characterization of the materials, where a is the positive electrode material without coating treatment, and b is the LiNi coated with metal oxide in Example 1 0.83 Mn 0.05 Co 0.12 O2 material.
[0019] Figure 2 LiNi coated with metal oxide in Example 1 0.83 Mn 0.05 Co 0.12 Comparison of the capacity retention rates of button cells assembled with O2 material as the positive electrode and lithium metal as the negative electrode after cycling for 200 weeks at -40°C at a rate of 0.1C / 0.2C.
[0020] Figure 3 LiNi coated with metal oxide in Example 1 0.83 Mn 0.05 Co 0.12 A button cell assembled with O2 material as the positive electrode and lithium metal as the negative electrode, and the rate performance graph tested at -40°C.
[0021] Figure 4 The button cell assembled with the material of Example 2 as the positive electrode and 50 micron lithium metal as the negative electrode, the 0.1C / 0.2C charge and discharge rate and data comparison chart measured in a blue power test cabinet at -40°C.
[0022] Figure 5 LiNi 0.83 Mn 0.05 Co 0.12 The charge and discharge curves of a button cell assembled with O2 material as the positive electrode and 50 micron lithium metal as the negative electrode at -40°C for different cycles are shown. Figure 4 for comparison.
[0023] Figure 6 The LiNi coated with metal oxide in Example 1 0.83 Mn 0.05 Co 0.12 The charge and discharge curves of a button cell assembled with O2 material as the positive electrode and 50 micron lithium metal as the negative electrode at different numbers of cycles tested at -40°C.
[0024] Figure 7 LiNi 0.83 Mn 0.05 Co 0.12 The discharge curves of a button cell assembled with O2 material as the positive electrode and 50 micron lithium metal as the negative electrode at different rates tested at -40°C.
[0025] Figure 8 The LiNi coated with metal oxide in Example 1 0.83 Mn 0.05 Co 0.12 The discharge curves of a button cell assembled with O2 material as the positive electrode and 50 micron lithium metal as the negative electrode at different rates tested at -40°C. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation methods. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.
[0027] Example 1 Preparation of LiNi coated with lithium tantalate 0.83 Mn 0.05 Co 0.12 O2 Dissolve 50 mg of tantalum ethoxide in 4 ml of ethanol solution and stir for 30 min; Take LiNi with a mass ratio of 100:2 to tantalum ethoxide 0.83 Mn0.05 Co 0.12 O2 material was added to another beaker containing 4 mg ethanol solution under ultrasound and ultrasound was applied for 15 min; Under ultrasound, a solution containing tantalum ethoxide is dropped into a solution containing a positive electrode material at a dropping speed of 2.5 mL / min. The mixed solvent was placed on a magnetic stirrer and heated and stirred at 80°C for 3 hours at a speed of 500 rpm. The solution was allowed to evaporate to obtain LiNi coated with lithium tantalate. 0.83 Mn 0.05 Co 0.12 O2; The ternary material coated with lithium tantalate was placed in a vacuum drying oven at 100°C for 14 hours, and then cooled naturally after heating; The lithium tantalate coated ternary material was calcined in an oxygen atmosphere at a temperature of 750°C, a time of 4, and a heating rate of 5°C / min.
[0028] Figure 1 a is the positive electrode material without coating treatment, b is the LiNi coated with metal oxide in Example 1 0.83 Mn 0.05 Co 0.12 SEM characterization of O2 material testing, LiNi after coating 0.83 Mn 0.05 Co 0.12 There is a coating on the surface of the O2 material, which fills the surface gaps, which reduces the contact area between the positive electrode and the electrolyte, thereby reducing side reactions.
[0029] Figure 2 The button cell assembled with the material obtained in Example 1 as the positive electrode and 50 micron lithium metal as the negative electrode, the 0.1C / 0.2C charge and discharge rate and data comparison measured in a blue power test cabinet at -40°C, Figure 1 It shows that the cycle stability of the coated samples is greatly improved at low temperatures compared with the uncoated samples, and the capacity retention rate is as high as 89.77% after 200 cycles.
[0030] Figure 3 The LiNi coated with metal oxide in Example 1 0.83 Mn 0.05 Co 0.12 The rate performance diagram of a button cell assembled with O2 material as the positive electrode and lithium metal as the negative electrode tested at -40°C. As shown in the figure, the rate performance of the sample after coating is improved.
[0031] Figure 5 LiNi 0.83 Mn 0.05 Co0.12 The charge and discharge curves of a button cell assembled with O2 material as the positive electrode and 50 micron lithium metal as the negative electrode at -40°C for different cycles are shown. Figure 4 for comparison.
[0032] Figure 6 The LiNi coated with metal oxide in Example 1 0.83 Mn 0.05 Co 0.12 The charge and discharge curves of button cells assembled with O2 material as the positive electrode and 50 micron lithium metal as the negative electrode at different cycles tested at -40°C show that the polarization decreases at low temperatures compared to the uncoated LiNi. Moreover, as the number of cycles increases, the charge and discharge voltage platforms are better than those of the uncoated LiNi. 0.83 Mn 0.05 Co 0.12 O2, indicating that this method has significantly improved the electrochemical performance at low temperatures.
[0033] Figure 7 LiNi 0.83 Mn 0.05 Co 0.12 The discharge curves of button cells assembled with O2 material as the positive electrode and 50 micron lithium metal as the negative electrode at different rates tested at -40°C are used as Figure 8 for comparison.
[0034] Figure 8 The LiNi coated with metal oxide in Example 1 0.83 Mn 0.05 Co 0.12 The discharge curves of button cells assembled with O2 material as the positive electrode and 50 micron lithium metal as the negative electrode at different rates tested at -40°C are shown in Figure 2. Figure 7 Compared with the uncoated positive electrode material, the discharge voltage platform is obviously better with the increase of the rate, indicating that the LiNi 0.83 Mn 0.05 Co 0.12 O2 material has better discharge performance in extremely cold temperatures.
[0035] Example 2 Preparation of LiNi coated with lithium tantalate 0.83 Mn 0.05 Co 0.12 O2 Dissolve 50 mg of tantalum ethoxide in 8 ml of ethanol solution and stir for 30 min; 2.5 g of LiNi 0.83 Mn 0.05 Co 0.12O2 was added to the solvent and ultrasound was continued for 30 min; The mixed solvent was placed on a magnetic stirrer and heated and stirred at 80°C for 3 hours at a speed of 500 rpm. The solution was allowed to evaporate to obtain LiNi coated with lithium tantalate. 0.83 Mn 0.05 Co 0.12 O2; The ternary material coated with lithium tantalate was placed in a vacuum drying oven at 100°C for 14 hours, and then cooled naturally after heating; The lithium tantalate coated ternary material was calcined in an oxygen atmosphere at a temperature of 750°C, a time of 4, and a heating rate of 5°C / min.
[0036] Figure 4 The button cell assembled with the material in Example 2 as the positive electrode and 50 micron lithium metal as the negative electrode was tested in a blue power test cabinet at -40°C for 0.1C / 0.2C charge and discharge rates and data comparison. Figure 4 It shows that compared with the samples that have not undergone step-by-step treatment, at low temperatures, the capacity of the battery in Example 2 that has not undergone step-by-step treatment drops significantly after 160 cycles, while the capacity retention rate of the positive electrode coated by step-by-step treatment in Example 1 is as high as 89.77% after 200 cycles, indicating that this method has a significant effect on improving the electrochemical performance of the battery at low temperatures.
[0037] Example 3 This embodiment provides a high-nickel ternary positive electrode material coated with a metal oxide, wherein the solute of the coating metal solution in step (1) is niobium ethoxide, and the rest is the same as in Embodiment 1.
[0038] Example 4 This embodiment provides a metal oxide-coated high-nickel ternary positive electrode material, wherein the high-nickel ternary positive electrode selected in step (2) is LiNi 0.8 Co 0.15 Al 0.05 O2, the rest is the same as in Example 1.
[0039] Example 5 This embodiment provides a high-nickel ternary positive electrode material coated with a metal oxide, wherein the ultrasonic time in step (2) is 10 minutes, and the rest is the same as in embodiment 1.
[0040] Example 6 This embodiment provides a high-nickel ternary positive electrode material coated with a metal oxide, wherein the ultrasonic time in step (2) is 20 minutes, and the rest is the same as in embodiment 1.
[0041] Example 7 This embodiment provides a metal oxide-coated high-nickel ternary positive electrode material, wherein the dropping speed in step (3) is 1.5 mL / min, and the rest is the same as in Embodiment 1.
[0042] Example 8 This embodiment provides a metal oxide-coated high-nickel ternary positive electrode material, wherein the stirring speed in step (4) is 700 rpm, and the rest is the same as in Embodiment 1.
[0043] Example 9 This embodiment provides a metal oxide-coated high-nickel ternary positive electrode material, wherein the stirring speed in step (4) is 800 rpm, and the rest is the same as in Embodiment 1.
[0044] Example 10 This embodiment provides a high-nickel ternary positive electrode material coated with a metal oxide, wherein the stirring and heating temperature in step (4) is 60° C., and the rest is the same as in Embodiment 1.
[0045] Embodiment 11 This embodiment provides a high-nickel ternary positive electrode material coated with a metal oxide, wherein the stirring and heating temperature in step (4) is 70° C., and the rest is the same as in Embodiment 1.
[0046] Example 12 This embodiment provides a high-nickel ternary positive electrode material coated with a metal oxide, wherein the stirring time in step (4) is 4 hours, and the rest is the same as in Embodiment 1.
[0047] Example 13 This embodiment provides a high-nickel ternary positive electrode material coated with a metal oxide, wherein the stirring time in step (4) is 5 hours, and the rest is the same as in Embodiment 1.
[0048] Embodiment 14 This embodiment provides a high-nickel ternary positive electrode material coated with a metal oxide, wherein the drying temperature in step (4) is 80° C., and the rest is the same as in Embodiment 1.
[0049] Embodiment 15 This embodiment provides a high-nickel ternary positive electrode material coated with a metal oxide, wherein the drying temperature in step (4) is 90° C., and the rest is the same as in Embodiment 1.
[0050] Example 16 This embodiment provides a metal oxide-coated high-nickel ternary positive electrode material, wherein the calcination temperature in step (5) is 720° C., and the rest is the same as in Embodiment 1.
[0051] Embodiment 17 This embodiment provides a metal oxide-coated high-nickel ternary positive electrode material, wherein the calcination temperature in step (5) is 780° C., and the rest is the same as in Embodiment 1.
Claims
1. A method for preparing a high-nickel ternary positive electrode material coated with a metal oxide, characterized in that: Here are the steps: (1) dissolving a solution containing a coated metal in an organic solvent under stirring conditions to obtain a solution containing a metal oxide; (2) adding high nickel ternary material powder to an organic solvent under ultrasonic operation, and ultrasonicating for 10 to 30 minutes to obtain a solution of high nickel ternary positive electrode material powder; (3) dripping a solution containing a metal oxide into a solution of a high-nickel ternary cathode material powder under ultrasonic operation to obtain a mixed solution; (4) heating the mixed solution under magnetic stirring conditions to evaporate the solvent, collecting the material, and drying it in a vacuum drying oven; (5) The dried material is placed in pure oxygen for calcination to obtain a metal oxide-coated high-nickel ternary positive electrode material.
2. The method for preparing the metal oxide-coated high-nickel ternary positive electrode material according to claim 1, characterized in that: The organic solvent in step (1) and step (2) is one of ethanol, hydroxymethane, N-methyl-2-pyrrolidone, N,N-dimethylformamide and isopropanol.
3. The method for preparing the metal oxide-coated high-nickel ternary positive electrode material according to claim 1, characterized in that: In the step (1), the solute of the solution containing the coating metal is one of tantalum ethoxide, zirconium ethoxide, niobium ethoxide and tungsten ethoxide.
4. The method for preparing the metal oxide-coated high-nickel ternary positive electrode material according to claim 1, characterized in that: The high nickel ternary positive electrode material is LiNi x Co y M 1-x-y O2, wherein M is one of Al, Mn, Mg, Ti, and W, and x≥0.8, 0<y≤1.
5. The method for preparing the metal oxide-coated high-nickel ternary positive electrode material according to claim 1, characterized in that: In the step (2), the molar ratio of the metal oxide in the solution containing the coated metal to the high-nickel ternary material powder is 0.5-3:
100.
6. The method for preparing the metal oxide-coated high-nickel ternary positive electrode material according to claim 5, characterized in that: In the step (2), the molar ratio of the metal oxide in the solution containing the coated metal to the high-nickel ternary material powder is 1-2:
100.
7. The method for preparing the metal oxide-coated high-nickel ternary positive electrode material according to claim 1, characterized in that: The dropping speed in step (3) is 1.5 to 3.0 mL / min.
8. The method for preparing the metal oxide-coated high-nickel ternary positive electrode material according to claim 1, characterized in that: In the step (4), the heating temperature is 50-80° C., the rotation speed is 500-1000 rpm, and the stirring time is 3-8 hours.
9. The method for preparing the metal oxide-coated high-nickel ternary positive electrode material according to claim 1, characterized in that: In the step (4), the vacuum drying temperature is 80 to 120° C., and the vacuum drying time is 10 to 18 hours.
10. The method for preparing the metal oxide-coated high-nickel ternary positive electrode material according to claim 1, characterized in that: In step 5, the calcination temperature is 600° C. to 800° C., the heating rate is 2° C. to 8° C. / min, and the calcination time is 3 to 8 hours.
Citation Information
Patent Citations
Ta surface doped high-nickel single-crystal positive electrode material and preparation method thereof
CN113066978A
Coating method for prolonging cycle life of high-nickel ternary positive electrode material
CN114300683A
Preparation method of synergistically modified ternary positive electrode material
CN118156451A
Cited By
Surface modification method and application of high-nickel ternary positive electrode material
CN120527389A